KONSEP PENDIDIKAN PADA KITAB ADI PARWA DALAM APLIKASINYA PADA PASRAMAN PRAKERTI BHUANA KELURAHAN BENG-KABUPATEN GIANYAR - I Made Dian Saputra; Gede Agus Budi Adnyana (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2021)
Hinduism is a religion that has a lot of literature or literary works which arefundamentally a form of text with values that can be used as a guide for life for its people. Thus,the various Hindu centers, which are scattered with different variants, have one distinctivefeature as a form of manuscript that tells humans in order to become better.One of them is the Adi Parwa book which contains a lot of the concept of HinduEducation as a whole. The studies conducted tend to analyze the Adi Parwa Book as anindependent manuscript without separate supporting parts and narratives. A fact shows thatAdi Parwa was built not with a single homogeneous plot, but with fragments and sequencesthat are related and unrelated to the main narrative. Thus it can be said that Adi Parwa is acollection of long narratives with many episodes that tell about different objects and subjects,with a more specific structural link between teachers and students. So Adi Parwa is moreprecisely a manuscript with many narratives, plots, characterizations, objects as the center,the focus of the story, and stands with many sacred mandates in it. This tends to be forgotten.Viewing Adi Parwa's study as an independent book with a single plot is a mistake. Because AdiParwa tells many things in many different plots, and ends with different accuracy. If the studyis only carried out by looking at Adi Parwa as a complete narrative with one plot, then we willnot find any values and mandates.